YB1 participated in regulating mitochondrial activity through RNA replacement - Gong, Weipeng; Zhang, Song (Frontiers in Oncology, 2023)
As a relic of ancient bacterial endosymbionts, mitochondria play a central role in cell metabolism, apoptosis, autophagy and other processes. However, the function of mitochondria-derived nucleic acids in cellular signal transduction has not been fully elucidated. Here, our work has found that Y-box binding protein 1 (YB1) maintained cellular autophagy at a moderate level to inhibit mitochondrial oxidative phosphorylation. Besides, mitochondrial RNA was leaked into cytosol under starvation, accompanied by YB1 mitochondrial relocation, resulting in YB1-bound RNA replacement. The mRNAs encoded by oxidative phosphorylation (OXPHOS) associated genes and oncogene HMGA1 (high mobility group AT-hook 1) were competitively replaced by mitochondria-derived tRNAs. The increase of free OXPHOS mRNAs released from YB1 complex enhanced mitochondria activity through facilitating themselves translation, but the stability of HMGA1 mRNA was impaired without the protection of YB1, both contributing to breast cancer cell apoptosis and reactive oxygen species production. Our finding not only provided a new potential target for breast cancer therapy, but also shed new light on understanding the global landscape of cellular interactions between RNA-binding proteins and different RNA species.